Evaluation of Small-Scale Providers of Water Supply and Sanitation Services in Peru - World Bank (Washington, DC, 2014)
The Water and Sanitation Program (WSP), administered by the World Bank, helps countries find sustainable solutions to ensure efficient delivery of the quality water supply and sanitation services the population demands. The WSP is carrying out a systematic analysis in several countries to identify the role of small-scale providers (SSP) of water and sanitation services to poor populations not served by public and private entities. The study also examines how these operators fit in and respond to sector policies and the organization of the sector in each country. The objective of this study is to identify the reasons for the existence of small-scale providers of water SSP in Peru and to evaluate the experience of these operators, with an emphasis on their coverage, service quality, costs and sustainability. The evaluation also includes proposals to improve service to the market traditionally served by SSP. The study was divided into three phases: (a) a sector assessment to determine why sector policies and financial and institutional resources have not produced service provision to the entire population, particularly to the segments served by SSP; (b) surveys in 14 communities with SSP and an analysis of responses to questions pertaining to legal, technical, market and financial aspects, as well as consumers' perceptions; and (c) sector policy recommendations with respect to SSP, and suggestions for priority projects to support better service delivery.